Tourist destinations and their call for management from local planning. An approach to the tourist product of the province of Gutierrez - Sanchez Castellanos, Sandra Milena (2021)
This article compiled the elements that gave way to both the construction of the Tourist Product of the Gutiérrez Province in the department of Boyacá (Colombia) and its management, from the strategic planning of tourism development in the territory. This scenario was generated after the events that prompted this destination to rethink the different sectors that converge in the characteristic tourist activity; from the organization of the key actors in the territory, to the consolidation of the municipality's flagship product A vision of the tourism product was proposed, from the local tourism planning and its interaction between the sectors that, especially driven by the private sector, redesigned the activity. This process was carried out through the development of four coordinated projects between different actors, starting with a diagnosis of the components of the destination for the development of the product and ending with its promotion at the regional and national levels.